Cashew Nutshell Waste as an Energy Feedstock: Analysis of the Potential for Combustion and Gasification - Micena, Raul Pereira [UNESP] (2024)
Considered an agricultural product of great socioeconomic interest in northeastern Brazil, the cashew nut has as one of its main by-products the kernel. This inner part of the nut is industrialized through processes that consume, most of the time, environmentally aggressive energy resources, such as firewood and LPG fossil gas. Being the nutshell a bio-waste of these processes, we evaluated the potential application of this material to replace firewood and LPG, in its solid state in natura and in the form of syngas resulting from its thermal gasification process. The cashew nut processing has a thermal fuel consumption between 2 and 7 GJ per ton of processed cashew kernel, depending on whether the fuel is LPG or firewood. The resulting emissions reach values between 142 and 727 kg of CO2eq per ton of processed kernel, respectively. Given the quantities of nutshell produced in the processing process, it was calculated that the nutshells have a potential to provide between 28.5 and 45.7 GJ per ton of kernel in the form of solid fuel. If gasified, they can provide up to 33.69 GJ per ton of kernel, values much higher than the energy needs of the processes involved. These results allow us to conclude that the nutshell has good potential for energy utilization in agro-industrial processes, both as a substitute for firewood and LPG gas.